Exploring the association between adoptive parents’ attachment orientations and adoptees’ emotional and behavioral difficulties: The role of parents’ self-compassion and mindful parenting - Rato, Maria Matilde Proença Paulo (2023)
Dissertação de Mestrado em Intervenções Cognitivo-Comportamentais em Psicologia Clínica e da Saúde apresentada à Faculdade de Psicologia e de Ciências da Educação